What every executive should know about cost-effective security (New York : Alexander Hamilton Institute, 1983)
The purpose of this manual is to convince the readers of two points: that security is a vital function which can actually add to your profits; and that effective security need not be expensive.
ne 29/06/2018
Loans
Keywords: Security measures--Management.